Multimodal Metaphor Approach to the Meaning-Making of the United Nations' Posters - Putu Dea Indah Kartini; Gede Primahadi Wijaya Rajeg; I Made Netra (CV. ULIL ALBAB CORP, 2024)
This study aims to identify the metaphors used in the images and textual elements of selected United Nations (UN) posters, analyze how these metaphors convey meaning, and understand the functions of the messages delivered. The data was sourced from the official Instagram account of the UN, @unitednations. The data were analyzed using a descriptive-qualitative approach with the application of multimodal metaphor theory by Forceville (2009) and visual grammar theory by Kress and Van Leeuwen (2020). The results indicate that the visual and verbal processes in these posters are complementary and work together to provide a cohesive message to the audience. The analysis reveals that the metaphors used in the posters serve to enhance the communication of complex global issues by making abstract concepts more relatable and understandable. This study contributes to the understanding of how multimodal metaphors in posters can be effectively used for global communication.